Students' Collaborative Problem Solving in Mathematics Classrooms An Empirical Study - Cao, Yiming (Perspectives on Rethinking and Reforming Education, 2024)
This open access book provides key insights into the social fundamentals of learning and indications of social interactive modes conducive and restrictive of that learning in China. Combining theoretical and technical advances in an innovative research design, this book focuses on collaborative problem solving in mathematics to increase the visibility of social interactions in teachers' designing, students' learning and teachers' instructional intervention. It also explores students' cognitive and social interaction as well as teacher intervention in students' group collaboration.